The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/s1047951117001019
|View full text |Cite|
|
Sign up to set email alerts
|

Is the medical treatment for arterial hypertension after primary aortic coarctation repair related to age at surgery? A retrospective cohort study

Abstract: Risk of medical treatment for hypertension was lowest when primary repair was carried out during the neonatal period, rising 10-fold if first operated on as a child. Knowing the likelihood of hypertension development depending on age of primary repair is useful for long-term surveillance and counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…The remaining full texts were requested via our library, but only 4 published in English were used. After consulting the full content of these 356 articles, only 17 fulfilled the inclusion criteria as set out above (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (Table 1).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The remaining full texts were requested via our library, but only 4 published in English were used. After consulting the full content of these 356 articles, only 17 fulfilled the inclusion criteria as set out above (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (Table 1).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…In our study patients with arterial hypertension were older and operated on at older age than normotensive subjects. The observations from other studies [22] reveal that younger age at operation is related to lower arterial pressure at follow-up; it is the best if treatment is applied before 9-10 years old. We did not observe the influence of type of surgery on development of arterial hypertension.…”
Section: Discussionmentioning
confidence: 88%
“…As reported elsewhere, currently CoAo is repaired at a very early age; in our series, the median age was 28 days, and about 80% were less than 12 months. Lillitos et al demonstrated that risk of medical treatment for hypertension was lowest when the primary repair was carried out during the neonatal period, with a 10‐fold increased risk if operated as a child. Thus, we speculate that the risk of late hypertension requiring treatment may be minimized by early repair of CoAo.…”
Section: Resultsmentioning
confidence: 99%